Self-assembly micro-nano fold structure, preparation method thereof, physical property measurement method and pressure sensor

By forming an opening pattern in the polymer material layer and depositing a metal layer, heating is used to induce the formation of a large-area self-assembled micro-nano wrinkle structure, which solves the problem of difficulty in preparing high-quality wrinkle structures in the existing technology, and improves the efficiency through optical scanning technology. Efficiency of material physical property measurement.

CN119365053APending Publication Date: 2025-01-24INSTITUTE OF PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411467906.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to prepare large-area high-quality fold structures, and there are problems of inefficiency in material screening and physical properties measurement.

Method used

By forming an opening pattern in the polymer material layer, the metal layer is deposited on it, the fold structure is used to induce it with heating, and at the same time, the directional deposition process and optical scanning technology are used for physical measurement.

Benefits of technology

The preparation of large -scale self -assembly micro -nanochromic structure is realized, the quality of the pleated structure and the performance of the pressure sensor are improved, the material screening and physical measurement process are simplified, and the efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365053A_ABST
    Figure CN119365053A_ABST
Patent Text Reader

Abstract

The invention relates to a self-assembled micro-nano wrinkle structure, a preparation method thereof, a physical property measurement method and a pressure sensor. The method for forming the fold structure comprises the following steps: forming a high polymer material layer on a first substrate; forming an opening pattern in the high polymer material layer; forming a metal layer on the high polymer material layer; and heating the metal layer to induce formation of a wrinkle structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to the field of microstructures, and more particularly, to a self-assembled micro-nano wrinkled structure and a preparation method thereof, a physical property measurement method using the micro-nano wrinkled structure, and a pressure sensor including the micro-nano wrinkled structure. Background Art

[0002] With the in-depth development of materials science research, the demand for three-dimensional structures at the micro-nano scale is increasing, and rapid and non-destructive material detection methods also need to be further developed. At the same time, functional micro devices are also a research hotspot. Wrinkles are surface fluctuations caused by mechanical instability caused by length mismatch between layered materials. The key to the preparation process of large-area, high-quality (uniform structure) wrinkled structures lies in the control of stress fields and the selection of highly elastic materials. However, most of the current methods use mechanical application to provide stress fields, which can only provide single or two axial stresses that are difficult to control, and uneven stress distribution may occur over a large area, making it difficult to form large-area, high-quality wrinkled structures. Therefore, new stress application methods should be developed to develop wrinkle structure preparation methods with strong controllability, high precision and cross-scale processing capabilities.

[0003] In addition, how to quickly screen suitable materials is a difficult point. As we all know, although high molecular polymers have good elasticity and a wide variety, they have disadvantages such as non-conductivity and a small temperature tolerance range, making it difficult to play a good role in application scenarios such as complex environments. Therefore, in recent years, many research teams have begun to devote themselves to the development of functional structural devices based on metal wrinkles. Metal materials, commonly used single metal materials such as Cu and Ag, are limited in variety, and it is difficult to regulate the periodicity of wrinkles by changing the physical properties of the materials; on the other hand, single metals often exist in the form of crystals, with poor elastic properties (0.5% elastic limit), which makes it difficult to meet the service requirements under high strain. The high-throughput research method through doping can provide multi-component and multi-ratio materials, but in the face of complex materials, there are characteristics of long test cycles and large amounts of data. At present, characterization and research are carried out by scanning point by point, and there are serious constraints on the test step length and characterization efficiency. When the step length is long, the time is short but it is easy to miss key information, and when the step length is small, the research efficiency will be greatly reduced. Therefore, there is an urgent need for new technical routes to provide a convenient and efficient high-throughput physical property characterization method. Summary of the invention

[0004] The present invention is proposed in view of the above problems.

[0005] One aspect of the present application provides a method for forming a wrinkle structure, comprising: forming a polymer material layer on a first substrate; forming an opening pattern in the polymer material layer; forming a metal layer on the polymer material layer; and heating the metal layer to induce formation of a wrinkle structure.

[0006] In one embodiment, the polymer material layer includes an elastic polymer material, and the metal layer includes a metal element or alloy in a crystalline or amorphous state.

[0007] In one embodiment, the opening pattern includes a plurality of openings regularly arranged and separated from each other in the polymer material layer, each opening has a circular or regular polygonal shape, and each opening extends a portion or all of the thickness of the polymer material layer.

[0008] In one embodiment, forming the metal layer on the polymer material layer includes: forming the metal layer using a directional deposition process, so that the metal layer on the polymer material layer and the metal layer in the opening pattern are discontinuous with each other.

[0009] In one embodiment, the thickness of the polymer material layer is in the range of 50 nm to 50 μm, preferably in the range of 0.1 μm to 10 μm. The thickness of the metal layer is in the range of 10 nm to 500 nm, preferably in the range of 50 nm to 200 nm.

[0010] In one embodiment, the heating temperature of the polymer material layer and the metal layer is in the range of 60°C to 150°C, preferably in the range of 80°C to 130°C.

[0011] Another aspect of the present application provides a wrinkle structure, comprising: a polymer material layer formed on a first substrate, wherein an opening pattern is formed in the polymer material layer; and a metal layer formed on the polymer material layer, wherein the metal layer is heated to induce formation of a wrinkle structure.

[0012] Another aspect of the present application provides a pressure sensor, comprising: a polymer material layer formed on a first substrate, wherein an opening pattern is formed in the polymer material layer; a metal layer formed on the polymer material layer, wherein the metal layer is heated to induce formation of a wrinkle structure; and interdigitated electrodes formed on a second substrate, wherein the interdigitated electrodes include a first electrode and a second electrode separated from each other, wherein the first substrate is arranged to be opposite to the second substrate so that the wrinkle structure is attached to the interdigitated electrodes to form a conductive path between the first electrode and the second electrode.

[0013] Another aspect of the present application provides a method for measuring the physical properties of an alloy material, comprising: forming a polymer material layer on a first substrate; forming a metal layer on the polymer material layer, the metal layer comprising an alloy material formed of multiple metals; heating the metal layer to induce formation of a wrinkle structure; measuring the height and width of the wrinkle structure; and calculating the physical properties of the alloy material based on the height and width of the wrinkle structure.

[0014] In one embodiment, calculating the physical properties of the alloy material based on the height and width of the wrinkle structure includes:

[0015] The elastic modulus of the alloy material is calculated based on the following formula:

[0016]

[0017] Where λ is the fold width, h is the thickness of the metal layer, E f is the elastic modulus of the alloy material, E s is the elastic modulus of the polymer material forming the polymer material layer, ν s is the Poisson's ratio of the polymer material, ν f is the Poisson's ratio of the alloy material and is determined as an approximation of the Poisson's ratio of the metal material included in the alloy material; and / or

[0018] The thermal expansion coefficient of the alloy material is calculated based on the following formula:

[0019]

[0020] Among them, α s is the thermal expansion coefficient of the polymer material, α f is the thermal expansion coefficient of the alloy material, ΔT is the difference between the heating temperature and the temperature before heating, and A is the wrinkle height.

[0021] In one embodiment, the contents of the multiple metals included in the metal layer vary basically continuously along a direction, and the method includes calculating the physical properties of the alloy material when the multiple metals have different contents by measuring the heights and widths of multiple wrinkles at different positions in the direction.

[0022] The above and other features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a flow chart of a method for preparing a wrinkled structure according to an embodiment of the present invention;

[0024] Figure 2 yes Figure 1 Schematic diagram of the structure formed in each step of the method shown;

[0025] Figure 3 is based on Figure 1 A photograph of an example of a wrinkled structure prepared when an opening pattern is formed in a polymer material layer by a method;

[0026] Figure 4is based on Figure 1 A photograph of an example of a wrinkled structure prepared by the method but without forming an opening pattern in the polymer material layer;

[0027] Figure 5 is a schematic structural diagram of a pressure sensor according to an embodiment of the present invention;

[0028] Figure 6 yes Figure 5 Schematic diagram of interdigital electrodes in a pressure sensor shown;

[0029] Fig. 7A and Figure 7B yes Figure 5 The principle schematic diagram of the pressure sensor shown;

[0030] Fig. 8A It is a three-dimensional topography of the wrinkle structure obtained by optical scanning;

[0031] Figure 8B is based on Fig. 8A The three-dimensional topography shown is a schematic diagram of measuring the height and width of wrinkles;

[0032] Fig. 9A is a schematic graph of wrinkle height and alloy material composition measured in a sample;

[0033] Fig. 9B is a schematic graph of wrinkle width and alloy material composition measured in a sample; and

[0034] Fig. 9C It is a bar graph showing the relationship between the elastic modulus of a sample and the alloy material composition. DETAILED DESCRIPTION

[0035] Exemplary embodiments of the present invention are described below with reference to the accompanying drawings.

[0036] Figure 1 is a flow chart of a method for preparing a large-area self-assembled micro-nano wrinkled structure according to an embodiment of the present invention. Figure 2 Shown in Figure 1 Schematic diagram of the structure formed in each step shown. Figure 1 and Figure 2 The method for preparing a large-area self-assembled micro-nano wrinkled structure may include: step S1, forming a polymer material layer 102 on a first substrate 101; step S2, forming an opening pattern in the polymer material layer 102; step S3, forming a metal layer 103 on the polymer material layer 102; and step S4, heating the metal layer 103 to induce formation of a wrinkled structure.

[0037] The substrate 101 may be an insulating substrate, a semiconductor substrate, or a conductive substrate, and may be a hard substrate, an elastic substrate, or a flexible substrate, which may be selected according to the specific application scenario of the prepared folded structure, and the present invention has no special limitation on this. For example, the substrate 101 may include, but is not limited to, a silicon nitride wafer, a silicon wafer, a silicon dioxide wafer, an aluminum oxide wafer, a glass wafer, a quartz wafer, a metal wafer such as a copper wafer, a plastic wafer, etc. Preferably, the substrate 101 has a smooth and clean surface for forming a multilayer structure thereon.

[0038] The polymer material layer 102 formed on the substrate 101 may include an elastic polymer material, which may be insulating or conductive. Because there are many types of elastic polymer materials, they are not listed here one by one, and suitable polymer materials can be selected according to application environments and performance requirements such as heat resistance and elasticity. In some embodiments, the material forming the polymer material layer 102 may include, for example, PDMS (polydimethylsiloxane) or a commonly used photoresist, such as PMMA, Zep glue, etc., or an ultraviolet photoresist such as AZ glue, SU8 glue, etc.

[0039] In one embodiment, the polymer material layer 102 may be formed on the first substrate 101 by spin coating. Specifically, a proper amount of liquid polymer material is dropped onto the first substrate 101 by a pipette, and then the first substrate 101 is rotated at high speed to form a uniform thin layer of the polymer material. If necessary, the first substrate 101 may be heated to accelerate the solidification or curing of the liquid polymer material. In another embodiment, a separately formed polymer material film may be transferred to the first substrate 101, and the two may be bonded to each other using glue.

[0040] The thickness of the formed polymer material layer 102 can be controlled according to the application needs. For example, the thickness of the formed polymer material layer 102 can be controlled by controlling the rotation speed and time of the first substrate 101. In some embodiments, the thickness of the polymer material layer 102 can be in the range of 50nm to 50μm, preferably in the range of 0.1μm to 10μm. It should be understood that the present application describes some specific parameters in order to fully and clearly disclose some specific embodiments so that those skilled in the art can implement the present invention. However, the scope of the present invention is not limited by these specific parameters, but under the guidance of the present application, those skilled in the art can select and adjust these parameter values ​​according to the actual application needs.

[0041] In step S2, various processes can be used to form an opening pattern 102a in the polymer material layer 102. In some embodiments, when the polymer material layer 102 is formed by a photoresist, the opening pattern 102a can be directly formed in the polymer material layer 102 by an exposure and development process. Exposure may include but is not limited to electron beam exposure, ultraviolet exposure, laser direct writing process, etc. The exposed photoresist layer is placed in a developer to remove the exposed or unexposed part (depending on the type of photoresist), thereby forming an opening pattern 102a, and then placed in a fixing solution for fixing. When the polymer material layer 102 is formed by a material other than a photoresist, a photoresist pattern layer can be formed on the polymer material layer 102, and then the polymer material layer 102 is etched under the protection of the photoresist pattern layer to form a desired opening pattern 102a. The etching method may adopt dry etching technology, such as ion milling etching, reactive ion etching, inductively coupled plasma reactive ion etching, etc., or may adopt wet etching technology, such as using chemical solutions such as hydrofluoric acid and potassium hydroxide to etch polymer materials, etc. 102.

[0042] The formed opening pattern 102a may include a plurality of openings regularly arranged and separated from each other in the polymer material layer 102, that is, the plurality of openings are arranged in a regular array, such as an array arranged in rows and columns. As described in detail below, the opening pattern 102a is used to induce the generation of a uniform wrinkle structure, so it is preferred that the plurality of openings are uniformly arranged in the polymer material layer 102, that is, the distances between adjacent openings are equal to each other, and the shape of each opening may be a circle or a regular polygon, such as an equilateral triangle, a square, a regular pentagon, etc. The size of each opening (such as a diameter or the longest diagonal) may be in the range of tens of nanometers to tens of micrometers, such as in the range of 100nm to 100μm, and the distance may be from several millimeters to several centimeters, such as in the range of 3mm to 2cm. It should be understood that these values ​​are only examples, and the size and distance of the openings may be selected and adjusted according to the thickness of the polymer material layer 102 and the metal layer 103 to be formed thereon, as well as the planar size of the entire sample. It should be noted that although Figure 2 The opening pattern 102 a is shown to extend the entire thickness of the polymer material layer 102 , but in some embodiments, the opening pattern 102 a may extend only a portion of the thickness of the polymer material layer 102 , ie, may not penetrate the polymer material layer 102 .

[0043] In step S3, a physical deposition method or a chemical deposition method can be used to directly deposit a metal layer 103 on the polymer material layer 102. Examples of deposition methods that can be used include, but are not limited to, thermal evaporation, electron beam evaporation, magnetron sputtering, laser pulse deposition, atomic layer deposition, and the like. When depositing the metal layer 103, the first substrate 101 can be placed on a sample stage in the deposition chamber, and the sample stage can be cooled, such as by water cooling, so that the first substrate 101 is kept below a certain temperature, such as generally below 60°C. The thickness of the deposited metal layer 103 can be in the range of 10nm to 500nm, and an appropriate thickness can be selected according to the selected metal material and the desired properties such as elasticity, toughness, etc. In some embodiments, the thickness of the metal layer 103 is preferably in the range of 50nm to 200nm. A metal layer that is too thin or too thick may not be conducive to forming a good wrinkle structure, which will be described in further detail below. In other embodiments, the separately formed metal layer 103 can also be transferred to the polymer material layer 102, and the two can be bonded to each other to be combined together.

[0044] In some embodiments, a directional deposition process may be preferably used to form the metal layer 103 on the polymer material layer 102, so that the metal layer on the polymer material layer 102 and the metal layer in the opening 102a are discontinuous with each other. Here, "directional deposition" is a different deposition process relative to "conformal deposition". In conformal deposition, the deposited metal layer will cover the sidewalls of the opening 102a, so that the metal layer on the polymer material layer 102 and the metal layer in the opening 102a are continuous with each other, and the resulting continuous metal layer is basically conformal with the surface used to deposit the metal layer; whereas in the directional deposition process, the metal material is deposited in a direction perpendicular to the substrate, so that the formed metal layer will not cover the sidewalls of the opening 102a, and a Figure 2 It should be noted that in order to avoid forming a continuous metal layer 103, the depth of the opening 102a should be greater than the thickness of the metal layer 103, for example, more than twice the thickness of the metal layer 103.

[0045] The metal layer 103 may include a metal element, such as Cu, Ag, etc., or may include an alloy, and the alloy may include an alloy of binary, ternary, quaternary or even higher-element materials. Throughout this application, the term "metal" may include an element or an alloy. In some embodiments, the metal layer 103 preferably includes an amorphous metal element or alloy. Compared with crystalline metal materials, amorphous metals not only have metallic characteristics such as good conductivity, high temperature resistance and toughness, but also exhibit the high elastic limit (2% elastic limit), high strength, corrosion resistance and wear resistance of amorphous materials due to the lack of long-range periodic structure. Therefore, it is more suitable for constructing a pleated device and helps to improve the performance of a pressure sensor formed using a pleated device. The metal layer 103 can have an amorphous structure by selecting appropriate materials and corresponding deposition processes, which will not be repeated here.

[0046] When the metal layer 103 includes an alloy material, the composition ratio of various elements can generally be uniform and constant throughout the metal layer 103. In other embodiments, the composition ratio of various elements in the metal layer 103 can also be adjusted as needed. For example, in one embodiment, when the metal layer 103 includes an alloy material formed by a first element and a second element, in the process of depositing the metal layer 103, the target material of the first element and the target material of the second element can be respectively located on both sides of the substrate 101, so that in the formed metal layer 103, along the direction from the first element target material to the second element target material, the content ratio of the first element gradually decreases, while the content ratio of the second element gradually increases, and the content ratio of each element basically changes continuously. When the metal layer 103 is formed by more elements, the content ratio of each element can be modulated in a similar manner.

[0047] In step S4, various heating methods may be used to heat the metal layer 103 to induce the formation of a wrinkled structure. For example, the first substrate 101 may be placed on a hot plate or in a heating chamber to be uniformly heated as a whole, or may be locally heated by laser irradiation or the like. Figure 2 The schematic diagram shows the undulating corrugated structure obtained after heating. Due to the elasticity of the polymer material layer 102, it can be deformed to well support the metal layer 103 on which the corrugated structure is formed. Therefore, it can be said that the polymer material layer 102 and the metal layer 103 form a composite corrugated structure. This structure has the characteristics of both polymer materials and metal materials, such as excellent elasticity, toughness (not easy to break), conductivity, etc., and can therefore be used to form a high-quality pressure sensor, which will be further discussed in detail below.

[0048] Although not limited to any theory, it is believed that the wrinkle structure induced in the metal layer 103 by heating is related to the difference in thermal expansion coefficients between the polymer material layer 102 and the metal layer 103 and the stress in the metal layer 103. Due to the difference in thermal expansion coefficients between the polymer material layer 102 and the metal layer 103, the thermal expansion coefficient of the metal material is generally much higher than that of the polymer material, so when heated, the metal layer 103 will expand, especially stretch in the plane, and because the polymer material hardly expands, the bonding interface between the two will exert stress on the expanded metal layer 103 to involve / hinder the expansion of the metal layer 103, and ultimately cause the generation of an undulating wrinkle structure in the metal layer 103 due to the imbalance of stress in the plane. When the metal layer 103 is uniformly heated, many tiny wrinkle structures with relatively uniform sizes will be generated in the plane of the metal layer 103. On the other hand, there is a certain internal stress in the metal layer 103 deposited in step S3, and heating will cause the internal stress in the metal layer 103 to be released, so when the heating is stopped and naturally cooled to room temperature, the metal layer 103 will not completely recover to the shape before heating, so the generated wrinkle structure will not disappear. Different from the traditional method of applying mechanical stress to generate a wrinkle structure, the heating method of the present application can induce the generation of a large-area self-assembled micro-nano wrinkle structure, improve the process efficiency, and compared with mechanical stress, the heating method can achieve better uniformity, which helps to produce a uniformly distributed high-quality wrinkle structure.

[0049] It should be understood that the opening pattern 102a in the metal layer 103 plays a role in releasing stress, and due to the regular arrangement of the opening pattern 102a, it can induce stress release in the metal layer 103, thereby producing a more evenly distributed wrinkle structure, which is beneficial for example in forming a high-quality pressure sensor.

[0050] It can also be understood that, in addition to the above factors, the thickness of the metal layer 103 may also affect the shape of the formed wrinkle structure. If the metal layer 103 is too thin, it may be difficult to produce a wrinkle structure; if the metal layer 103 is too thick, a large-scale wrinkle structure may be produced, which is not conducive to the formation of a pressure sensor, because the pressure sensor is expected to have a large number of uniformly distributed tiny wrinkle structures. Although the thickness of the metal layer 103 can be selected according to the material of the amorphous metal, in general, the thickness of the metal layer 103 can be in the range of 10nm to 500nm, preferably in the range of 50nm to 200nm. In addition, the heating temperature can also be adjusted to achieve the regulation of the wrinkle morphology, thereby affecting the sensing ability of the pressure sensor. In general, when uniformly heated by a thermal field, the heating temperature of the polymer material layer 102 and the metal layer 103 is preferably within the heat-resistant temperature range of the polymer material, or below the glass transition temperature of the polymer material, because the melting temperature of the metal is generally much higher than the glass transition temperature of the polymer material. If local heating is performed by laser irradiation, for example, the heating temperature may slightly exceed the glass transition temperature of the polymer material, because the heating time is short and the thermal conductivity of the amorphous metal is good, so it is difficult for a large amount of heat to be transferred to the polymer material below the amorphous metal layer. In some embodiments, the heating temperature may be in the range of 60°C to 150°C, preferably in the range of 80°C to 130°C. Depending on the heating method, the heating time may be in the range of 2 seconds (e.g., local laser heating) to 30 minutes (e.g., uniform heating by a hot plate), and for overall uniform heating in a hot environment, it may be in the range of 2 minutes to 30 minutes, preferably in the range of 2 minutes to 15 minutes.

[0051] An example of preparing a corrugated structure is described below.

[0052] Step S1: A silicon wafer substrate was prepared in advance and cleaned in oxygen plasma for 10 seconds, then UV photoresist AZ 1500 was spin-coated on the cleaned silicon wafer at a speed of 3000 r / min for 60 seconds, and then baked on a hot plate at 100° C. for 1 minute.

[0053] Step S2: Expose the sample obtained in step S1 using a laser direct writing process, wherein the predetermined pattern to be exposed is set to be isolated and periodically arranged squares, and after the exposure is completed, develop the sample using a developer and then fix the sample using a fixer.

[0054] Step S3: using a multi-target co-deposition method, Cu and Zr are sputtered simultaneously in a vacuum chamber of a magnetron sputtering machine, and a Cu-Zr amorphous alloy with a single composition ratio is deposited on the polymer AZ 1500, with a thickness of about 100 nanometers.

[0055] Step S4: placing the sample obtained in step S3 on a heating table and heating it at 100° C. for 2 min can induce a whole wrinkled amorphous alloy film.

[0056] In another comparative example, the pleated structure is formed by the same process as above, but step S2 is omitted, that is, the square opening pattern is not formed. The photos of the obtained pleated structure are shown in Figures 3 and 4, respectively. Figure 4 Among them Figure 3 is a photograph of a wrinkle structure prepared when an opening pattern 102a is formed. Figure 4 is a photograph of a wrinkle structure prepared without forming the opening pattern 102a. Figure 3 and Figure 4 It can be clearly seen that when the opening pattern 102 a is formed, a fold structure with more uniform distribution and regular directionality is formed in the metal layer 103 due to the multiple openings arranged regularly.

[0057] Figure 5 FIG. 1 is a schematic diagram of the structure of a pressure sensor according to an embodiment of the present invention. Figure 5 As shown, the pressure sensor includes a first substrate 101 and a second substrate 201 facing each other, and the corrugated structure formed by the metal layer 103 on the first substrate 101 is attached to the interdigital electrodes on the second substrate 201, wherein the interdigital electrodes include a first electrode 202 and a second electrode 203 separated from each other. The first electrode 202 and the second electrode 203 in the interdigital electrodes are connected to each other through the corrugated structure formed by the metal layer 103 to form a conductive path. Figure 5 It is shown that the first substrate 101 is located above the second substrate 201 , but the second substrate 201 may also be placed above the first substrate 101 .

[0058] Figure 6 An embodiment of an interdigitated electrode formed on a second substrate 201 is shown. As shown in the figure, the interdigitated electrode includes a first electrode 202 and a second electrode 203 that are separated from each other and present an interdigitated shape, a first electrode terminal 204 connected to the first electrode 202, and a second electrode terminal 205 connected to the second electrode 203. The second substrate 201 can be any suitable substrate, such as an insulating substrate, including a glass substrate, a silicon dioxide substrate, a quartz substrate, a sapphire substrate, etc. The interdigitated electrodes can be formed of a metal or alloy material with good electrical conductivity, such as Cu, Ag, etc. It should be understood that the shape of the interdigitated electrodes is not limited to Figure 6The shape shown in the figure can have any other shape, such as but not limited to spiral shape. Any method can be used to form the interdigital electrodes on the second substrate 201. For example, a metal layer can be blanket deposited on the second substrate 201, and then the shape of the interdigital electrodes is etched out. For another example, a photoresist layer is first formed on the second substrate 201, and the opening pattern shape of the interdigital electrodes is formed in the photoresist layer by exposure and development processes, and then the metal layer is directionally deposited in the opening and on the photoresist layer. The photoresist layer can be formed thicker so that the metal material deposited in the opening is discontinuous with the metal material deposited on the photoresist layer. Finally, the photoresist layer and the metal material thereon are easily removed using, for example, acetone, thereby leaving the interdigital electrode structure in the opening pattern. This process is also referred to as a lift-off process.

[0059] Fig. 7A and Figure 7B Shows Figure 5 The working principle of the pressure sensor is shown in Figure 2. Fig. 7A When the pressure between the first substrate 101 and the second substrate 201 increases, the wrinkle structure is squeezed and deformed, causing the area of ​​the metal layer 103 in contact with the interdigital electrodes to increase, and the resistance value between the first electrode 202 and the second electrode 203 to decrease. Therefore, by measuring the resistance value between the first electrode 202 and the second electrode 203, the magnitude of the pressure can be determined. Figure 7B The relationship between pressure (using a weight as an example) and sensor resistance value is shown. When the pressure increases, the resistance value decreases. Therefore, the pressure sensed by the pressure sensor can be determined by measuring the resistance between the first electrode terminal 204 and the second electrode terminal 205 of the interdigitated electrode.

[0060] The present application also provides a method for measuring the physical properties of alloy materials using a corrugated structure. The corrugated structure can be formed using the above method, which will not be repeated here. When used for physical property measurement, it is not necessary to form an opening pattern in the polymer layer 102. Among them, the metal layer 103 forming the corrugated structure can be formed by an alloy material (this is because the physical properties of metal elements are generally known, but the method of the present invention can also be used to measure the physical properties of metal elements), such as binary, ternary or more alloy materials. The composition ratio of the alloy material can be consistent throughout the metal layer 103, or can change uniformly along a predetermined direction, so that the method of the present invention can measure the physical properties of alloy materials with different composition ratios, which improves the measurement efficiency. For example, as mentioned above, the composition ratio in the alloy can be continuously changed by setting the position of the deposition target relative to the substrate, or other methods can be used to change the composition ratio in the alloy continuously or discontinuously.

[0061] After the wrinkle structure is prepared, the height and width of the wrinkle feature can be measured. In one embodiment, an optical characterization system can be used to quickly obtain the three-dimensional morphological features of the wrinkle structure, for example, an optical confocal microscope can be used, or an optical system such as a white light interferometer or a self-built optical path that can achieve three-dimensional information scanning can be used. Fig. 8A An example of a three-dimensional morphology image of a wrinkle structure obtained by optical scanning is shown. The characteristic parameters of the wrinkles, including height and width, can be obtained by rapid optical three-dimensional scanning of the sample surface, and ultimately the physical properties of the alloy material can be calculated, which will be described in detail below.

[0062] Figure 8B An example of wrinkle characteristic parameters collected by optical scanning is shown, including wrinkle height (also referred to as amplitude) and wrinkle width (also referred to as wavelength). As mentioned above, the self-assembled wrinkle structure can be an alloy wrinkle of a single component ratio, or an alloy wrinkle with a high-flux component ratio and gradual evolution. Due to differences in the properties and thickness of the alloy material, the width / wavelength of the self-assembled wrinkle structure can be any value from tens of nanometers to tens of microns, and the height / amplitude can be any value from tens of nanometers to several microns. The characteristic values ​​of a specific area conform to the Gaussian distribution, and the characteristic statistics of different areas will evolve in the case of a high-flux component ratio. Therefore, by measuring the height and width of multiple wrinkles at different positions (corresponding to different component ratios), the physical properties of alloy materials with different component ratios can be calculated respectively. The composition ratio of the alloy material in the obtained sample can be measured and determined by X-ray diffraction (XRD) or energy dispersive spectrometer (EDS).

[0063] The physical properties of the alloy material forming the corrugated structure can be calculated based on the height and width of the corrugated structure. In some embodiments, the elastic modulus of the alloy material is calculated based on the following formula (1):

[0064]

[0065] Where, λ is the fold width, h is the thickness of the metal layer 103, and E f is the elastic modulus of the alloy material, E s is the elastic modulus of the polymer material forming the polymer material layer, ν s is the Poisson's ratio of the polymer material, ν f is the Poisson’s ratio of the alloy material. E s and ν s is a known quantity, λ can be measured and determined, and h can be determined when the metal layer 103 is deposited, or can be determined by thickness measurement after deposition. Since the Poisson's ratio of materials is generally small, ν fIt can be determined as an approximate value (such as an average value) of the Poisson's ratio of the metal material included in the alloy material. Therefore, the elastic modulus E of the alloy material can be calculated based on the above formula: f .

[0066] In another embodiment, the thermal expansion coefficient of the alloy material may also be calculated based on the following formula:

[0067]

[0068] Among them, α s is the thermal expansion coefficient of the polymer material, α f is the thermal expansion coefficient of the alloy material, ΔT is the difference between the heating temperature and the temperature before heating, and A is the wrinkle height.

[0069] As mentioned above, in the case where the component ratio in the metal layer 103 changes, the above physical properties of the alloy materials with different component ratios can be calculated by measuring the heights and widths of multiple wrinkles at different positions (corresponding to different component ratios), which helps to improve the measurement efficiency and thus screen out the desired alloy material. Taking the Cu-Zr amorphous alloy prepared in the above example as an example, Fig. 9A The figure shows the curve of the wrinkle height measured by the above optical method as a function of Cu content. Fig. 9B The graph showing the variation of the wrinkle width with the Cu content measured by the above optical method is shown. Fig. 9C The elastic modulus of the alloy material corresponding to different Cu contents calculated based on the above measurement data is shown. Therefore, after the wrinkle structure is prepared, the method of the present invention can automatically perform optical scanning, feature data acquisition and physical property calculation processes with the help of relevant equipment, greatly improving the efficiency of physical property measurement.

[0070] The present invention provides a method for preparing a self-assembled micro-nano wrinkle structure, based on the physical property optical detection method and sensor structure design thereof, the self-assembly processing mechanism is to induce stress through an external physical field, realize the self-assembly of micro-nano size wrinkles by means of the stress difference between two layers of materials, and induce the generation of a regularly arranged and uniform wrinkle structure by introducing an opening as a stress release area, thereby greatly improving the quality of the wrinkle structure and the performance of a pressure sensor formed by the wrinkle structure. By adjusting the film thickness, the intensity of the external physical field or patterning the polymer film, the wrinkle morphology can be modulated to obtain alloy wrinkles of different lateral wavelengths and longitudinal heights. The method has simple equipment, low cost, controllable and efficient processing, and can quickly realize large-area micro-nano scale wrinkle processing. In addition, the method has no additional loss to the material, and the wrinkle morphology can reflect the intrinsic physical properties of the material. Therefore, by means of fast optical scanning means to obtain three-dimensional information of the wrinkles, the elastic modulus and thermal expansion coefficient of the material can be quickly identified through the wrinkles. This method is fast and universal, and can realize uninterrupted testing of high-throughput continuous films. At the same time, sensing is achieved through the high elasticity of the wrinkles and the change in the area of ​​connection between the interdigital electrodes caused by deformation. The device has a simple structure, clear principle and excellent performance, and can be designed and implemented according to the needs of microelectronic devices in different application scenarios and conditions. This broadens the application field of materials and wrinkles, and will also play an important role in enriching application scenarios such as flexible devices and electronic skin in the future.

[0071] The modulus optical detection method based on self-assembled micro-nano wrinkles and the sensor structure design provided by the present invention have at least the following technical advantages:

[0072] 1. Through the induction of external physical fields, a stress difference is generated between the polymer material layer and the target material layer, thereby realizing the self-assembly of three-dimensional wrinkles. The processing mechanism is simple, and the wrinkle morphology can be regulated by controlling the material thickness, the intensity of physical field stimulation and the patterning of the polymer material;

[0073] 2. The processing technology adopted by the present invention is simple, efficient and low-cost, and has low damage to the material. The three-dimensional morphology of the wrinkles can also use optical means to quickly characterize the intrinsic physical quantities of the material, realize the rapid detection of the material properties, and provide a new idea for studying composite materials with continuous changes in multi-element high-throughput components;

[0074] 3. The present invention adopts a micro-nano conductive pleat structure as a micro sensor component, which not only utilizes the excellent conductive properties of the material, but also gives play to the deformation ability and adjustability of the pleats, thereby improving the performance of existing metal components in the sensing field, and providing strong support for the future application of conductive pleats in micro devices and electronic skin.

[0075] Unless the context clearly requires otherwise, throughout the specification and claims, the words "comprise", "comprising", "including", "comprising", etc. should be interpreted in an inclusive sense, rather than an exclusive or exhaustive sense. That is, the meaning is "including but not limited to". The word "connected" as generally used herein refers to two or more elements that can be directly connected or connected through one or more intermediate elements. As generally used herein, the word "connected" refers to two or more elements that can be directly connected or connected through one or more intermediate elements. In addition, when used in this application, the words "herein", "above", "below" and words of similar meanings should refer to the entirety of this application rather than to any particular part of this application. Where the context permits, the word "or" refers to a list of two or more items, which covers all of the following interpretations of the word: any item in the list, all items in the list, and any combination of items in the list.

[0076] Furthermore, unless otherwise specifically stated or understood in the context of use, conditional language used herein, such as "can," "may," "might," "could," "for example," "for example," "such as," and the like, is generally intended to convey that certain embodiments include, while other embodiments do not include, certain features, elements, and / or states. Thus, such conditional language is generally not intended to imply that one or more embodiments require features, elements, and / or states in any way, or that one or more embodiments must include logic for making decisions, with or without author input or prompting, that such features, elements, and / or states are included or will be performed in any particular embodiment.

[0077] Although certain embodiments have been described, these embodiments are presented only by way of example and are not intended to limit the scope of the present disclosure. In fact, the novel facilities, methods, and systems described herein may be embodied in various other forms; in addition, various omissions, substitutions, and changes may be made to the forms of the methods and systems described herein without departing from the spirit of the present disclosure. For example, although blocks are presented in a given arrangement, alternative embodiments may perform functions similar to different components and / or circuit topologies, and may delete, move, add, subdivide, combine, and / or modify some blocks. Each of these blocks may be implemented in a variety of different ways. Any suitable combination of the elements and actions of the various embodiments described above may be combined to provide further embodiments. The attached claims and their equivalents are intended to cover these forms or modifications that fall within the scope and spirit of the present disclosure.

[0078] The above description has been given for the purpose of illustration and description. In addition, this description is not intended to limit the embodiments of the present invention to the forms disclosed herein. Although a number of example aspects and embodiments have been discussed above, those skilled in the art will recognize certain variations, modifications, changes, additions and sub-combinations thereof.

Claims

1. A method for forming a wrinkled structure, comprising: forming a polymer material layer on the first substrate; forming an opening pattern in the polymer material layer; forming a metal layer on the polymer material layer; The metal layer is heated to induce formation of a corrugated structure.

2. The method of claim 1, wherein: The polymer material layer comprises an elastic polymer material. The metal layer includes a metal single substance or an alloy in a crystalline or amorphous state.

3. The method of claim 1, wherein: The opening pattern includes a plurality of openings regularly arranged and spaced apart from each other in the polymer material layer, each opening having a circular or regular polygonal shape, and each opening extending a portion or all of the thickness of the polymer material layer.

4. The method of claim 1, wherein: Forming a metal layer on the polymer material layer comprises: The metal layer is formed by using a directional deposition process, so that the metal layer on the polymer material layer and the metal layer in the opening pattern are discontinuous with each other.

5. The method of claim 1, wherein: The thickness of the polymer material layer is in the range of 50 nm to 50 μm, preferably in the range of 0.1 μm to 10 μm. The thickness of the metal layer is in the range of 10 nm to 500 nm, preferably in the range of 50 nm to 200 nm.

6. The method of claim 1, wherein: The heating temperature of the polymer material layer and the metal layer is in the range of 60°C to 150°C, preferably in the range of 80°C to 130°C.

7. A pleated structure comprising: A polymer material layer is formed on the first substrate, wherein an opening pattern is formed in the polymer material layer; as well as a metal layer formed on the polymer material layer, Therein, the metal layer is heated to induce formation of a wrinkled structure.

8. A pressure sensor comprising: A polymer material layer is formed on the first substrate, wherein an opening pattern is formed in the polymer material layer; a metal layer formed on the polymer material layer, the metal layer being heated to induce formation of a wrinkled structure; forming interdigital electrodes on a second substrate, the interdigital electrodes comprising a first electrode and a second electrode separated from each other, The first substrate is arranged to face the second substrate, so that the corrugated structure is attached to the interdigitated electrodes to form a conductive path between the first electrode and the second electrode.

9. A method for measuring the physical properties of an alloy material, comprising: forming a polymer material layer on the first substrate; forming a metal layer on the polymer material layer, wherein the metal layer comprises an alloy material formed by a plurality of metals; heating the metal layer to induce formation of a wrinkled structure; measuring the height and width of the pleated structure; as well as The physical properties of the alloy material are calculated based on the height and width of the corrugated structure.

10. The method of claim 9, wherein: Calculating the physical properties of the alloy material based on the height and width of the wrinkle structure includes: The elastic modulus of the alloy material is calculated based on the following formula: Where λ is the fold width, h is the thickness of the metal layer, E f is the elastic modulus of the alloy material, E s is the elastic modulus of the polymer material forming the polymer material layer, ν s is the Poisson's ratio of the polymer material, ν f is the Poisson's ratio of the alloy material and is determined as the approximate value of the Poisson's ratio of the metallic material(s) covered; and / or The thermal expansion coefficient of the alloy material is calculated based on the following formula: e=(a s -a f )ΔT, Among them, α s is the thermal expansion coefficient of the polymer material, α f is the thermal expansion coefficient of the alloy material, ΔT is the difference between the heating temperature and the temperature before heating, and A is the wrinkle height.

11. The method of claim 10, wherein: The contents of the multiple metals included in the metal layer vary substantially continuously along a direction, and the method includes calculating the physical properties of the alloy material when the multiple metals have different contents by measuring the heights and widths of multiple wrinkles at different positions in the direction.